Optical properties of thin films ZNO+10 % ITO on the substrate of anodic aluminum oxide - N. I. Mukhurov; S. V. Denisiuk; A. N. Chumakov; A. A. Shevchenok; L. V. Baran; A. G. Karoza; T. F. Raichenok; N. A. Bosak; A. A. Ivanov; H. Zhang; G. Yu (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
ZnO thin films of zinc oxide doped with 10 % ITO (indium tin oxide) on anodic aluminum oxide substrates are formed in vacuum during high-frequency repetitively pulsed laser deposition. The morphology of films on porous and non-porous surfaces of substrates was studied by atomic force microscopy. The optical properties of the films in the visible, near, and middle IR regions of the electromagnetic radiation spectrum, the Raman spectra, and also the features of the photoluminescence characteristics have been experimentally investigated. Zinc oxide films can be used in optoelectronic transducers, as luminescent material, in the form of transparent electrodes, sensitive layers of gas and biological sensors, catalysts, X-ray and gamma-radiation detectors.